Retrofit Proposal for a 70-Year-Old Educational Building in a High-Seismicity Zone - Apaza, Diego (2025)
This article analyses the structural behaviour of an educational pavilion more than 70 years old in a highly seismic area, with damage to beams and columns attributed to the current use of the roof as a warehouse, in addition to having a high probability of collapse according to the FEMA P-154 seismic vulnerability study. Diamond extractions were carried out based on the ASCE 41-06 standard to obtain the compressive strength of the columns and beams. After the tests, linear and nonlinear analysis were performed based on the E.030 and ASCE 41-17 standards, respectively. The structural modelling confirmed non-compliance with the maximum distortion of 7/1000 allowed by the standard for the Y-axis gantry system. Therefore, RC jacketing was proposed as a reinforcement alternative according to the UNAM reinforcement guide and the IS 15988:2013 standard. The encasement of columns along the Y-axis reduced the drift by 58%, while the encasement of beams resulted in a 45% reduction. However, when implemented separately, neither of the seen casements met the regulatory limit, prompting the adoption of a combined encasement solution, which achieved an 80% reduction. Whereas the pushover analysis indicated that in the event of frequent and occasional earthquakes, the reinforced structure would be fully operational, which shows the importance of developing a reinforcement plan at the superstructure level addressed in this research, which not only offers a reinforcement solution, but also serves as a reference for similar initiatives in other countries.